Efeito da alamandina no remodelamento cardíaco induzido pela constrição da aorta transversa em camundongos - Mário de Morais e Silva (2018)
Introduction: Alamandine, a peptide formed by the decarboxylation of Ang-(1-7) aspartate or by the hydrolysis of Ang A by the angiotensin-converting enzyme 2, has recently been identified as the newest component of the renin-angiotensin system (RAS). Through interaction with its receptor, MrgD, alamandine showed cardioprotective effects. Although the involvement of various components of classical RAS in the genesis and progression of cardiac remodeling is well known, little is known about the effects of alamandine. Objective: To evaluate the effects of alamandine on cardiac remodeling induced by transverse aortic constriction (TAC) in mice. Materials and Methods: Male wild-type C57BL/6J mice were used between 10-12 weeks and 23g mean weight (CEUA 349/2016). For the experimental procedure, the animals were divided into SHAM (operated), TAC (operated) and TAC + ALA (operated and treated with alamandine - 30 μg / kg / day, by gavage). After 14 days of treatment, the animals were submitted to echocardiography and euthanized for collection of the left ventricle (LV). Results: The histological result demonstrated that the oral administration of alamandine prevents the development of cellular hypertrophy and reduces the deposition of total and perivascular collagen, evaluated through the Masson trichrome. Through DHE, we demonstrated that alamandine reduces the production of reactive oxygen species (ROS) in the LV of the animals, 14 days after the TAC. Through western blot analysis we have demonstrated that alamandine decreases the expression and phosphorylation of known TAC-induced markers of cardiac remodeling, such as ERK1/2, TGF- and MMP-2. The results also suggest an increase in the performance of the intracellular Ca2+ machinery provoked by the treatment with alamandine, in addition to promoting a high expression of SERCA2, increased the phosphorylation levels of phospholambam (PLN) Thr17. Conclusions: Our results showed that oral treatment with alamandine reduces changes in different parameters associated with TAC-induced ventricular remodeling and has anti-hypertrophic, antifibrotic effects, reduces expression of classic markers of cardiac remodeling, increases expression of SERCA2 and increases the phosphorylation levels of PLN. Therefore, this work helps to understand the role of alamandine in cardiac remodeling induced by pressure overload and provides a basis for the development of new studies that clarify the role of this peptide in cardiovascular diseases.